Determining redundancy in water distribution networks using percolation method in simulating pipe failure during a seismic event - Gonzales, Alfredo Miguel P. (Animo Repository, 2022)
Water distribution networks are the lifeline of civil society, and the disruption of these lifelines due to inevitable disasters like an earthquake can threaten and affect the community's overall well-being. Thus studying the pipelines in earthquake-prone areas is of utmost importance. In this regard, analyzing water distribution networks under failure conditions has long been a popular topic in order to predict the reliability of these buried pipes during an earthquake. Consequently, the redundancy of a system is related to its reliability, meaning improving the redundancy can enhance the system's reliability. By measuring the redundancy, researchers can gain insight into the vulnerability of a particular lifeline system when an earthquake happens. Therefore it is appropriate to measure the redundancy of a system to help mitigate seismic risk on lifeline structures. Based on Hoshiya et al. (2004), the Redundancy Index RE defined via Shannon's information entropy can be an index to represent the redundancy of a system. Wherein it plays a crucial role in choosing the best alternative for designing a system or in finding the best damage mitigation measure against earthquake hazards by utilizing specific simulation methods such as the Monte Carlo simulation. However, this paper uses a new approach to analyze these water distribution networks. This was done by investigating the failure process of a network using Percolation Theory. In this new view, a network failure can be regarded as a percolation process by gradually removing links in the system to simulate a link failure event. To test the proposed methodology, the Monte Carlo simulation and the Percolation method were applied to a published water distribution network, specifically the Kobe Network, and a hypothetical water network. The Percolation method was found to be a viable alternative to the Monte Carlo simulation in measuring the redundancy of a lifeline network because it adheres to the system's general logic. Accordingly, the Percolation method can correctly simulate an earthquake occurrence and generate accurate Redundancy Index (RE) values.